2019
DOI: 10.1080/03007995.2018.1552407
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of endoscopic eradication therapy for management of dysplasia arising in patients with Barrett’s oesophagus in the United Kingdom

Abstract: Background and Aims: Endoscopic eradication therapy (EET) is the first line approach for treating Barrett's Esophagus (BE) related neoplasia globally. The British Society of Gastroenterology (BSG) recommend EET with combined endoscopic resection (ER) for visible dysplasia followed by endoscopic ablation in patients with both low and high grade dysplasia (LGD and HGD). The aim of this study is to perform a cost-effectiveness analysis for EET for treatment of all grades of dysplasia in BE patients. Methods: A Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Average proton pump inhibitor (PPI) costs based on UK NHS (National Health Service) tariffs were adjusted into the model [31]. Unit costs for healthcare interventions were based on the NHS national payment tariffs for 2019/20 [32].…”
Section: Costs and Resource Usementioning
confidence: 99%
“…Average proton pump inhibitor (PPI) costs based on UK NHS (National Health Service) tariffs were adjusted into the model [31]. Unit costs for healthcare interventions were based on the NHS national payment tariffs for 2019/20 [32].…”
Section: Costs and Resource Usementioning
confidence: 99%
“…This trial was designed to derive accuracy data and the sensitivity used is from a per protocol analysis that includes inadequate samples without a repeat examination to provide a conservative, base case. We assumed that the confirmatory endoscopy with biopsy that follows a positive TFF3 test result had an effective sensitivity and specificity of 1 (gold-standard) for the purposes of the model, in line with assumptions taken by previous economic models [ 16 , 17 , 20 ]. This approach takes into account the face validity of a negative endoscopy test in that clinicians typically do not re-order endoscopy following negative findings, even though the sensitivity of endoscopy is less than 100%.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated mean and standard deviation costs for both arms for each cost component and all components combined ( Table 3 ). Utilities and disutilities were derived from the literature (see Appendix) [ 20 , [23] , [24] , [25] ]. Disutilities were applied to stricture (2 weeks), perforation, EMR and RFA surgery (4 weeks), chemotherapy (4.5 months), and esophagectomy (3 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cost-effectiveness analysis was conducted for endoscopic eradication therapy (EET) for treatment of all grades of dysplasia in Barrett’s oesophagus patients [ 102 ]. EET for patients with LGD and HGD arising in Barrett’s oesophagus was deemed as cost-effective compared to endoscopic surveillance alone (lifetime £3,006 per QALY gained) by Pollit et al [ 102 ] The authors further concluded that as the time elapses, the treatment becomes more cost-effective. The 5-year financial impact to the UK National Health Service (NHS) of introducing EET is £7.1 m [ 102 , 103 ].…”
Section: Introductionmentioning
confidence: 99%